Numerical Simulation Study on Hydrodynamic Characteristics of Offshore Floating Photovoltaics - Shuting Sui; Lu Cao; Yun Gao; Zhongyan Huo; Qi Chen (Journal of Marine Science and Engineering)
With the development of renewable energy and the utilization of marine resources, large-scale offshore floating photovoltaics have gradually attracted widespread attention. In order to develop offshore floating photovoltaics and promote sustainable development, it has become necessary to explore the hydrodynamic characteristics of floating photovoltaic units and floating arrays. In this work, based on the viscous flow theory, the Computational Fluid Dynamics (CFD) and the discrete element method (DEM) methods are used to analyze the hydrodynamics of the floating body unit of offshore floating photovoltaics. The influencing factors include mooring length, mooring radius, and floating unit length. In addition, the hydrodynamic performance of the floating body unit and the floating body array under different wave heights and periods is also discussed to explore the influence of environmental loads on the floating body unit and the floating body array. The results indicate that the mooring tension exhibits an opposite trend with the surge and heave motions when the mooring line length and radius are varied. The motion is found to be more pronounced when the floating body unit length is 0.4 times the wavelength. The heave motion of the floating body unit exhibits a strong linear relationship with wave height, increasing by 0.01 m for every 0.015 m increase in wave height. The motion of the floating body units on both sides connected to the mooring lines decreases as the array length increases.